Cardiac autonomic responses to different tasks in office workers with access to a sit-stand table – a study in real work setting. Issue 3 (4th March 2021) - Brusaca, Luiz Augusto; Barbieri, Dechristian França; Beltrame, Thomas; Milan-Mattos, Juliana Cristina; Catai, Aparecida Maria; Oliveira, Ana Beatriz
Abstract: The aim of this study was to characterise the cardiac autonomic modulation of different office tasks performed by office workers with access to a sit-stand table. Heart rate variability (HRV) of 24 office workers was measured for two hours during three days in the last week of sit-stand table use. HRV indexes and the percentage of heart rate reserve (%HRR) were calculated during computer and non-computer work tasks while sitting or standing, non-computer tasks away from the work desk, and informal work breaks. All cardiac autonomic responses demonstrated a statistically significant interaction effect between the tasks (all p  < 0.05) except for the logarithmically-transformed high frequency power (ln HF ms 2 ; p  = 0.14). Tasks performed while standing and away from the desk had higher sympathetic modulation; in addition, the observed higher %HRR demonstrated that these tasks were more physically demanding in comparison to other tasks. Practitioner Summary: Prior reports indicated benefits based on alternated body postures using sit-stand table. Nevertheless, the cardiac autonomic responses of different tasks performed by office workers are unknown. This cross-sectional study showed that different tasks stimulate the cardiac autonomic nervous system in different ways, which could bring positive effects to the cardiovascular system.